The influence of uncertain expectations on Chinese rural residents’ consumer behavior decisions: Theoretical analysis and empirical test - Han, Lina; Liu, Xiaofei; Ma, Shusheng (Frontiers in Psychology, 2023)
As the pandemic continuously, the global economy is faced with great uncertainties. Economic uncertainties will result in consumers’ unstable environment expectations, thus affecting enterprises’ investment and financing decisions and household consumption decisions. The paper established a consumption model that affects Chinese farmers through empirical analysis, research results show that consumers’ income, consumption, consumption habits, liquidity constraints and precautionary savings jointly produce the feelings of uncertainty, which will lead to irrational expectations, intensify the consumption behavior of rural residents short-sighted finally. Rural residents will “rationally” choose between consumption and savings with their income to accomplish their phased consumption goals and tend to make savings against major events, reduce their consumption. Finally, the consumption behavior shows the characteristics that prudence and declining consumption tendency. Therefore, we shall carefully analyze the factors influencing rural residents’ consumption, put forward corresponding policies and measures, and thus enable the beneficent cycle of “promoting rural consumption – driving the supply-side growth – enhancing high-quality economic development”.